HUBUNGAN KANDUNGAN NITRAT DAN FOSFAT TERHADAP PERTUMBUHAN BIOMASSA BASAH ECENG GONDOK DI RAWA KONGSI SUMATERA UTARA (Relations Nitrate and Phosphate on The Growth of Hyacinth Wet Biomass in Kongsi Swamp North Sumatra) - Yessy Christanty; Ternala Alexander Barus; Desrita Desrita (AQUACOASTMARINE, 2016)
The rapid growth of water hyacinth and high durability made plant growth is extremely difficult to control. This study aimed to determine the effect of nitrate and phosphate content of the relationship to the gowth of biomass wet hyacinth different locations in the waters Rawa Kongsi during an interval of two weeks. The research was conducted in March to April 2016. Length parameter is water hyacinth plant height, weight parameter consist of fresh weight of water hyacinth, and parameter number consists of the amount of water hyacinth leaves. Water quality parameters measured were dissolved oxygen, pH, temperature, brightness, nitrate and phosphate. The results obtained through the measurement of dissolved oxygen water quality is 1,6 mg/l-4 mg/l, pH is 6,3-6,6, water temperature is 30ºC-32ºC, brightness values is 42-119,5 cm. Nitrate values at Station I, II, and III is 0,25-0,73 mg/l; <0,001-2,09 mg/l; <0,001-2,4 mg/l. Phosphate values at Station I, II, and III is <0,001-0,019 mg/l; <0,001-0,026 mg/l; <0,001-0,032 mg/l. At station III gives better results on the growth of biomass compared to treatment at another location. The highest growth of water hyacinth biomass is found in the observation of the 2nd with biomass wet is 70.6 g and relative growth rate is 3.56% g/day.Keywords : Nitrate, Phosphate, Rawa Kongsi, Water Hyacinth, Wet BiomassGrowth